The Value of Informal Peace Committees as a Developmental Strategy to Deal with Post-Conflict in Zimbabwe - Chivasa, Norman (Southern African Journal of Social Work and Social Development, 2023)
In this article, I investigate the extent to which community-based initiatives such as informal peace committees can serve as vehicles for developmental social work practice to promote community empowerment and capacity development in Zimbabwe. The formation of self-initiated peace committees by Zimbabwean communities demonstrates local agency, self-reliance and resilience. This type of local agency resulted in community members working together to unite, participate and form a peacebuilding committee. The study was based on action research data from Ward 8 in the Seke District, in which 42 male and female adults participated. Given the study’s participatory nature, 14 informants took on multiple roles, including co-planning, co-designing and establishing a ward-level peace committee. The findings revealed that informal peace committees have a close relationship with developmental social intervention strategies that seek to deal with development challenges such as poverty, inequality, and violence and, the major one, community development. These attributes reflect the strengths and empowerment potential that developmental social work can explore to increase the impact of informal peace committees at the community level in the Seke District and beyond.